Physical and genetic attributes of Red Jungle fowl - VIJH, R K; KUMAR, ST BHARANI; MISHRA, BINA; SOOD, SUSHIL; RATAN, SANDEEP; TANTIA, M S (The Indian Journal of Animal Sciences, 2011)
The Red Jungle fowl is considered to be a progenitor of modern chicken. It is found in wild in Haryana, Himachal Pradesh, Uttarakhand, Asom, Tripura, Manipur and in isolated pockets of Madhya Pradesh and Andhra Pradesh states of India. The data on 25 microsatellites was generated on Red Jungle fowl. The data revealed a good degree of heterozygosity (0.579) at molecular level. The mean number of alleles per locus was 6.8. The effective number of alleles were 3.9 which pointing towards a large number of alleles to be present at very low frequency. Sixteen of the 25 loci were not in Hardy Weinberg Equilibrium providing information for the existence of population structure. The genetic base of the red jungle fowl maintained in the Pheasantry is sufficiently large as revealed by the tests for genetic bottle neck and heterozygosity values.